2011
DOI: 10.1016/j.vetmic.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Viral and antibody HEV prevalence in swine at slaughterhouse in Italy

Abstract: 1Hepatitis E is an acute disease of humans caused by a small RNA virus, Hepatitis E virus (HEV). In 2 recent years, an increasing number of autochthonous human infections have been reported in 3 industrialized countries. Genotype 3 is the main HEV type circulating in swine, and is also reported 4 in sporadic cases of hepatitis E in humans worldwide. To date one serotype has been described. We 5 have conducted a survey to detect antibodies against HEV in 48 swine at a slaughterhouse in 6Northern Italy, using EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
83
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 58 publications
17
83
2
1
Order By: Relevance
“…HEV replication without serological evidence of HEV infection in pigs has been related to recent infection when HEV RNA was detected in liver or bile. On the other hand, when it was detected only in stools, it was suggested a possible transient intestinal presence of the virus without replication after ingestion [35]. This pattern was found in eight pigs in this study.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…HEV replication without serological evidence of HEV infection in pigs has been related to recent infection when HEV RNA was detected in liver or bile. On the other hand, when it was detected only in stools, it was suggested a possible transient intestinal presence of the virus without replication after ingestion [35]. This pattern was found in eight pigs in this study.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, several studies had reported that detection of HEV RNA in the liver samples was less frequent than in feces or bile [5]. The latter is the sample where HEV RNA has been found more frequently [35,40]. It is possible that in the present study seronegative animals with positive PCR only in feces had also HEV RNA detectable in their bile, but we cannot confirm this because it was not collected.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The high levels of HEV detected in pigs from different countries (Clayson et al, 1995;de Deus et al, 2006;Baechlein et al, 2010) suggests that they could be carriers of HEV, and that this virus is a zoonosis transmitted to humans through water contaminated with pig feces or through contaminated viscera intended for consumption (La Rosa et al, 2010). However, swine HEV infection is asymptomatic; thus, it is difficult to determine when the infection peaks in order to optimize the sensitivity of tests for the virus (Di Bartolo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%